Approximate inference of Bayesian networks through edge deletion - Thornton, Julie Ann (Kansas State University, 2005)
Bayesian networks are graphical models whose nodes represent random variables and whose edges represent conditional dependence between variables. Each node in a Bayesian network is equipped with a conditional probability function that expresses the likelihood that the node will take on different values given the values of its parents. A common task for a Bayesian network is to perform inference by computing the marginal probabilities of each possible value for each node. In this thesis, I introduce three new algorithms for approximate inference of Bayesian networks that use edge deletion techniques. The first reduces a network to its maximal weight spanning tree using the Kullback-Leibler information divergence as edge weights, and then runs Pearl’s algorithm on the resulting tree. Because Pearl’s algorithm can perform inference on a tree in linear time, as opposed to the exponential running time of all general exact inference algorithms, this reduction results in a tremendous speedup in inference. The second algorithm applies triangulation pre-processing rules that are guaranteed to be optimal if the original graph has a treewidth of four or less, and then deletes edges from the network and continues applying rules so that the resulting triangulated graph will have a maximum clique size of no more than five. The junction tree exact inference algorithm can then be run on the reduced triangulated graph. While the junction tree algorithm has an exponential worst-case running time in the size of the maximum clique in the triangulated graph, placing a bound on the clique size effectively places a polynomial time bound on the inference procedure. The third algorithm deletes edges from a triangulation of the original network until the maximum clique size in the triangulated graph is below a desired bound. Again, the junction tree algorithm can then be run on the resulting triangulated graph, and the bound on the maximum clique size will also polynomially bound the inference time. When tested for efficiency and accuracy on common Bayesian networks, these three algorithms perform up to 10,000 times faster than current exact and approximate techniques while achieving error values close to those of sampling techniques.
Keywords: Computer science; Bayesian networks; Computer Science (0984)